Multilevel Analysis of Determinants of Stunting Incidence in Children Under 5 Years in Malaka Regency, East Nusa Tenggara - Yosefa Sarlince Atok; Roslin Evelina Margaretha Sormin; Nabilah Nurul Ilma (Journal of Ners and Midwifery, 2022)
Stunting is still a global nutritional problem. Stunting is a picture of the occurrence of chronic nutritional problems. Stunting caused by multiple factors, especially if it occurs in the first 1000 days of birth. Malaka Regency is one of the regions in NTT that recorded an increase in the percentage of stunting, from the previous 25% to 30% with the number of children experiencing stunting in Malaka currently reaching 4,909 people. With this number, Malaka is in 11th place with stunting in NTT (Malaka District Health Office, 2020). The purpose of the study was to determine the determinants of stunting in children under five in Malaka Regency. Research design. This research is analytic observational. This research is an observational analytic. The approach is case control and using a multilevel model which is one of the analytical techniques to determine the relationship between various variables in health with the Stata-13 program. This research was conducted by simple random sampling. The sampling technique used in this study. The sampling technique used in this study was stratified random sampling. The method used at the first level was to randomly select 10 villages in the district of Malaka, the second level to randomly select 25 integrated health care (IHC). Eight research subjects will be taken from each integrated service post so that the sample studied is 200 research subjects. Data was collected using a questionnaire and height measurement using a microtoise measuring instrument. The results of this study indicate that the factors causing stunting are exclusive breastfeeding (55.5%), Basic Sanitation (61.5%), Parenting (67.5%), and early marriage (32.0%). The results of this study indicate that the causes of stunting based on these variables have a significant difference (p < 0.05). Recommendations for health workers conduct socialization and counseling about exclusive breastfeeding, the importance of hygiene practices in daily life including caring for children, maximizing the community-based total sanitation program and conducting socialization related to the influence of early marriage.